Impact of Oral Diseases on the Quality of Life of Public Service Workers in Port Harcourt, Nigeria - Aikins, EA; Ordinioha, B (Journal of Orofacial Research, 2015)
Background: The oral health impact profile-14 (OHIP-14) scale is a valid, reliable and globally accepted tool for comprehensive measure of self-reported dysfunction, discomfort and disability attributed to oral conditions. The objective of this study was to evaluate subjectively the impact of oral disease on the quality of life of public service workers in Port Harcourt, Rivers State, Nigeria. Materials and methods: The study was a cross-sectional study conducted among public service workers in Port Harcourt, Rivers State, Nigeria. A total of 638 participants were selected using multistage sampling technique. Data were collected using pre-tested self-administered questionnaires containing information on biodemographics, dental service utilization and OHIP-14 variables. Analysis of OHIP-14 was done using the simple count and additive method on statistical package for social sciences spread sheet. Results: About 20% of the participants had OHIP score > 14. A total of 143 (22.4%) participants had utilized dental services in the past, 62.4% of this had OHIP score > 14. The impact as a result of oral health status experienced among the participants was ‘self-consciousness’, 62.3%; ‘painful aching’, 44.3% and ‘uncomfortable to eat’ 32.8%. There was no significant difference in quality of life in relation to gender, age educational status and salary grade level. Conclusion: Oral disease had a negative impact on quality of life; this impact was greater in the psychological and physical domain of the OHIP-14 scale. Respondents who reported greater impact of oral disease on their quality of life utilized dental services more frequently compared to those who reported less impact.